Nucleotide binding as an allosteric regulatory mechanism for Akkermansia muciniphila β-N-acetylhexosaminidase Am2136. (31st December 2022) - Li, Chang-Cheng; Yi, Huan; Wang, Yan-Mei; Tang, Xin-Yue; Zhu, Yi-Bo; Song, Ying-Jie; Zhao, Ning-Lin; Huang, Qin; Mou, Xing-Yu; Luo, Gui-Hua; Liu, Tong-Gen; Yang, Gang-Long; et al.
ABSTRACT: β- N -acetylhexosaminidases (EC3.2.1.52), which belong to the glycosyl hydrolase family GH20, are important enzymes for oligosaccharides modification. Numerous microbial β- N -acetylhexosaminidases have been investigated for applications in biology, biomedicine and biotechnology. Akkermansia muciniphila is an anaerobic intestinal commensal bacterium which possesses specific β- N -acetylhexosaminidases for gut mucosal layer colonization and mucin degradation. In this study, we assessed the in vitro mucin glycan cleavage activity of the A. muciniphila β- N -acetylhexosaminidase Am2136 and demonstrated its ability that hydrolyzing the β-linkages joining N -acetylglucosamine to a wide variety of aglycone residues, which indicated that Am2136 may be a generalist β- N -acetylhexosaminidase. Structural and enzyme activity assay experiments allowed us to probe the essential function of the inter-domain interactions in β23-β33. Importantly, we revealed that the hydrolysis activity of Am2136 was enhanced by nucleotides. We further speculated that this activation mechanism might be associated with the conformational motions between domain III and IV. To our knowledge, this is the first report of nucleotide effector regulated β- N -acetylhexosaminidase, to reveal its novel biological functions. These findings contribute to understanding the distinct properties within the GH20 family and lay a certain foundation to develop controllable glycan hydrolyzing catalysts. Abbreviations : OD600 - optical cell densities at 600 nm; LB - Luria–Bertani; IPTG - isopropyl β-D-1-thiogalactopyranoside; PMSF - phenylmethanesulfonyl fluoride; rmsd - root mean square deviation; GlcNAc - N-acetyl-β-D-glucosamine; GalNAc - N-acetyl-β-D-galactosamine; Gal - galactose